Development of a nano-satellite micro-thruster system - Do, Trong Chinh (2011)
Nanosatellite refers to an artificial satellite that has a mass of less than 10 kg and small dimensions such as 10cm x 10cm x 30cm. With the increasing interest in nanosatellite due to its low cost and simplicity, the thrusters possess simple, scalable, and low power characteristics are preferred to study. Hall Thruster is one of the best candidates to use for spacecraft as it is rather simple to manufacture, miniature among the plasma-ion engines. The report will show the design of an 11 mm channel miniature Hall Thruster (TAL type) prototype, namely NYT-11, based on MHT-9 designed by Noah Z. Warner (MIT) with modifications in materials chosen and complexity reductions in the anode. The dimensions of NYT-11 seem to approach the possible minimum with the magnet size and normal machining capability available in Singapore. Therefore, NYT-11 could be used for study, demonstration, reference etc… There should be a further research on micro propulsion to reduce more on the dimensions of the thruster if we want to integrate thruster in the nanosatellite. On the other hand, colloid thruster seems to be the ideal thruster for tiny size satellite in term of high precision control, low thrust, simple, light weight, low power, and high efficiency. Their specific impulses are possibly in the range of 1000s to 4000s. There are many institutes researching on the Colloid Thruster such as Tsinghua, MIT, Standford, Busek Company etc... A simple single needle colloid thruster testing was set up for demonstration in this project.